Effectiveness of cocoa beans (theobroma cacao l.) extract gel 8% and 16% in the healing of wistar rats (rattus norvegicus) gingiva incision wound - Chairunas; Munifah Abdat (Journal of Dentomaxillofacial Science, 2022)
Objective: To determine the effectiveness of 8% and 16% cocoa bean extract gel in the healing of Wistar rats gingival incision wound. Methods: Cocoa beans were extracted using the maceration method, diluted with a concentration of 8% and 16%, and the addition of CMC-Na as gel basis. The 24tailed mice are divided into 6 mouse-tails of treatment 1 given the 8% cocoa bean extract gel, 6-tails of treatment 2 given the 16% cocoa bean extract gel, 6-tailed mice positive groups given the drug Oxoferin solution 0,001%, and 6-tails of negative group given aquades. The treatment and wound length assessment of rats were carried out on the 1st day, 3rd day, 5th day, 7th and 10th days, then dieutanasia on day 10 using ether anesthesia and carried out the cutting of the mandibular bone using the gingival tissue to wound re-epithelialization observation with a microscope (Olympus BX-41) 200X magnification. Results: One-way ANOVA and Post-HOC LSD tests presented a significant difference in the length of Wistar rats gingival wound closure between the treatment group that applied 16% cocoa bean gel extract, the negative and positive control groups, while between the 8% gel extract, the negative and positive control groups showed insignificant differences. Mean gingival incision wound re-epithelialization of each group on day 10 was 24.57 µm, 28.93 µm, 50.63 µm, 48.03 µm respectively. Conclusion: The 16% cocoa bean extract gel treatment is effective in healing the gingival incision wound of Wistar rats after applied for 10 days.